Interactive theorem proving second International Conference, ITP 2011, Berg en Dal, The Netherlands, August 22-25, 2011, proceedings - Eekelen, Marko van; Geuvers, Herman; Schmaltz, Julien; Wiedijk, Freek (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Interactive Theorem proving, ITP 2011, held in Berg en Dal, The Netherlands, in August 2011. The 25 revised full papers presented were carefully reviewed and selected from 50 submissions. Among the topics covered are counterexample generation, verification, validation, term rewriting, theorem proving, computability theory, translations from one formalism to another, and cooperation between tools. Several verification case studies were presented, with applications to computational geometry, unification, real analysis, etc.